Comparative analysis of cloud and fog environment based on network usage and cost of execution using Ifogsim - Alam, Mohammad Saqibul; Jabin, Sadia Jebunnesa; Alam, Ajmain (BRAC University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.